(untitled) (ModaPalavra e-periódico, 2023)
Compressive stockings are mainly produced in order to treat and improve the lives of people with venous diseases and circulatory problems. The present study refers to the way in which design, as an interdisciplinary research field, can contribute to improve the quality of products and, consequently, their usability. An investigation of use occurred through a questionnaire with 122 users of compressive stockings. The research identified the user’s profile, as much as factors about learnability, efficiency, and satisfaction. It was also possible to highlight the motives of likes and dislikes about the device. Therefore, this article contributes to the project of stockings and emphasizes the need for research that contributes to more ergonomic, inclusive and adaptive products.